ANALISIS CATEGORY ADVERTISING EXPENDITURE DAN CONSUMER MEDIA HABIT DI MEDIA TELEVISI DAN MEDIA CETAK - Zifwen Zifwen; Ujang Sumarwan; MD Djamaludin (School of Business, Bogor Agricultural University (SB-IPB), 2006)
The purpose of the study is to identify the category of advertising expenditure and media habit on media advertising, especially on television and print ad such as newspapers, magazines and tabloids. The Data were collected from Nielsen Media Research (NMR) data base from a number of cities in Indonesia, such as Jakarta,Surabaya, Bandung, Semarang, Surabaya, Yogyakarta, Bali, Medan,Palembang and Makassar. There are three different type of data used to acquire the secondary data for the study: (1) Telescope (data collected for rating analysis) January 1st, 2005 to March 31st, 2005, (2) Print scope (data collected from the readership of magazines, tabloids and newspaper) January 1st, 2004 to December 31st, 2004 and (3) Ad quest (data collected from advertising expenditure for all categories). The data were collected, calculated and analyzed from January 1st, 2002 to December 31st, 2004. The purpose of the study is to uncover the trend of advertising budget from all categories on the television and print ads, in order to describe the consumption tendency of the people within advertising media. Index analysis and Biplot were used to analyze the data. Based on the result of advertising expenditure analysis of data, showing that all categories were completely different in the utilization of the media for advertisement. Some categories used mix media to support their campaign and others used a single media. Characteristic of the categories were strongly involved in the decision making in way of choosing and using the advertising media. The result of consumer media analysis found that the people habit were completely different and unique in media consumption. Different of age, sex and social economic status can create a different habit in term of hobbies and desire within the channel, programme, newspaper, magazines and the tabloids. Finally, to create an effective and efficient advertising activity, integrated between analyzed competitors (advertising expenditure) and target audience must be carried out in one unit of work form.